Having Difficulties Reading the Facial Expression of Older Individuals? Blame It on the Facial Muscles, Not the Wrinkles - Grondhuis, Sabrina N.; Jimmy, Angela; Teague, Carolina; Brunet, Nicolas M. (Frontiers in Psychology, 2021)
Previous studies have found it is more difficult identifying an emotional expression displayed by an older than a younger face. It is unknown whether this is caused by age-related changes such as wrinkles and folds interfering with perception, or by the aging of facial muscles, potentially reducing the ability of older individuals to display an interpretable expression. To discriminate between these two possibilities, participants attempted to identify facial expressions under different conditions. To control for the variables (wrinkles/folds vs facial muscles), we used Generative Adversarial Networks (GAN) to make faces look older or younger. Based upon behavior data collected from 28 individuals, our model predicts that the odds of correctly identifying the expressed emotion of a face reduced 16.2% when younger faces (condition 1) are artificially aged (condition 3). Replacing the younger faces with natural old-looking faces (Condition 2), however, results in an even stronger effect (odds of correct identification decreased by 50.9%). Counterintuitively, making old faces (Condition 2) look young (Condition 4) results in the largest negative effect (odds of correct identification decreased by 74.8 % compared with natural young faces). Taken together, these results suggest that both age-related decline in the facial muscles’ ability to express facial emotions and age-related physical changes in the face, explain why it is difficult to recognize facial expressions from older faces; the effect of the former, however, is much stronger than that of the latter. Facial muscle exercises, therefore, might improve the capacity to convey facial emotional expressions in the elderly.